(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
Communicative Language Teaching (CLT) has gained popularity as an effective approach to teaching English as a second or foreign language. This paper explores the key principles and methods of CLT and examines its effectiveness in enhancing students’ communicative competence and language fluency. The paper also discusses the challenges and potential limitations of using CLT in the English language classroom.